Immune Checkpoint Blockade for Metastatic Uveal Melanoma: Re-Induction following Resistance or Toxicity - Koch, Elias; Petzold, Anne; Wessely, Anja; Dippel, Edgar; Gesierich, Anja; Gutzmer, Ralf; Hassel, Jessica C.; Haferkamp, Sebastian; Kähler, Katharina C.; Knorr, Harald; Kreuzberg, Nicole; Leiter, Ulrike; et al. (Cancers, 2022)
Re-induction with immune checkpoint blockade (ICB) needs to be considered in many patients with uveal melanoma (UM) due to limited systemic treatment options. Here, we provide hitherto the first analysis of ICB re-induction in UM. A total of 177 patients with metastatic UM treated with ICB were included from German skin cancer centers and the German national skin cancer registry (ADOReg). To investigate the impact of ICB re-induction, two cohorts were compared: patients who received at least one ICB re-induction (cohort A, n = 52) versus those who received only one treatment line of ICB (cohort B, n = 125). In cohort A, a transient benefit of overall survival (OS) was observed at 6 and 12 months after the treatment start of ICB. There was no significant difference in OS between both groups (p = 0.1) with a median OS of 16.2 months (cohort A, 95% CI: 11.1–23.8) versus 9.4 months (cohort B, 95% CI: 6.1–14.9). Patients receiving re-induction of ICB (cohort A) had similar response rates compared to those receiving ICB once. Re-induction of ICB may yield a clinical benefit for a small subgroup of patients even after resistance or development of toxicities.
CRIS-Team Scopus Importer:2022-01-28
Keywords: CTLA-4; Immune checkpoint blockade; PD-1; Re-induction; Toxicity; Treatment resistance; Uveal melanoma